PENGARUH INTERVENSI PENYULUHAN GIZI DENGAN MEDIA ANIMASI TERHADAP PERUBAHAN PENGETAHUAN DAN SIKAP TENTANG ANEMIA PADA REMAJA PUTRI - Sutrio Syakir (ARGIPA (Arsip Gizi dan Pangan), 2018)
Iron deficiency anemia is the most common problem in Indonesia. One of attempt to overcome the problem of anemia is through education using the animation so that the message will be longer and better to be remembered because it used more sense and a stronger impression. This research objective was to measure the influence of nutrition education with animation media on knowledge and attitude change about anemia of adolescence girls at high school in Bandar Lampung. This research was conducted at high school girls in Bandar Lampung City in May-September 2017. This research used Pre-experimental with a one-group pretest-posttest design. Paired t-test was done by analyzing the variable of knowledge and attitude, which is measured before and after given nutrition counseling with animation media. Data were collected using questionnaire and research subjects were 300 subjects. The results showed there was a change of knowledge and attitude score after the intervention was done by using animation media (p<0,05). Keywords: Knowledge, Attitude, Anemia, Animation Media